Stiffness, intralimb coordination, and joint modulation during a continuous vertical jump test - Dal Pupo, J.; Ache Dias, J.; Ghedini Gheller, R.; Detanico, D.; dos Santos, S. G. (Sports Biomechanics, 2013)
This study analysed the modulation of jump performance, vertical stiffness as well as joint and intralimb coordination throughout a 30-s vertical jump test. Twenty male athletes performed the test on a force plate while undergoing kinematic analysis. Jump height, power output, ground contact time, vertical stiffness, maximum knee and hip flexion angles, and coordination by continuous relative phase (CRP) were analysed. Analysis of variance was used to compare variables within deciles, and t-tests were used to compare CRP data between the initial and final jumps. Results showed reduction in jump height, power output, and vertical stiffness, with an increase in contact time found during the test. Maximum knee and hip flexion angles declined, but hip angle decreased earlier (10-20% of the test) than knee angle (90-100%). No changes were observed in CRP for thigh-leg coupling when comparing initial and final jumps, but the trunk-thigh coupling was more in-phase near the end of the test. We conclude that fatigue causes reduction in jump performance, as well as changes in stiffness and joint angles. Furthermore, changes in intralimb coordination appear at the last 10% of the test, suggesting a neuromotor mechanism to counterbalance the loss of muscle strength.